Vine (Vitis vinifera L.) leaves as a functional ingredient in pistachio calisson formulations. (October 2019) - Jridi, Mourad; Abdelhedi, Ola; Kchaou, Hela; Msaddak, Lotfi; Nasri, Moncef; Zouari, Nacim; Fakhfakh, Nahed
Abstract: Vine ( Vitis vinifera L.) leaves powder (VLP) was characterized in terms of functional and chemical properties and used as an ingredient in a pistachio calisson formulation. The total phenolics and flavonoids contents, phenolic compounds profile as well as techno-functional characteristics of the VLP were measured. The sensory properties, color, mass loss and lipid oxidative stability of calissons enriched with VLP were also determined. VLP contained a high amount of insoluble dietary fibers, improving its fat and water absorption capacities. Liquid chromatography analysis of VLP extracts allowed the identification of 7 flavonoids and 5 phenolic acids. Quercetrin (quercetin-3- O -rhamonoside) was the major compound (875 μg/g extract) followed by rutin (quercetin-3- O -rutinoside) (384 μg/g extract). VLP was incorporated at two substitution levels (3 and 5%) in the pistachio calisson formulation. Results showed that calisson enrichment with VLP did not alter the sensory attributes. Interestingly, VLP addition also resulted in the reduction of mass loss and oxidative degradation of the pastry product during storage. The study suggested that VLP incorporation in a pistachio calisson formulation not only added nutraceutical value, but also improved its quality. Graphical abstract: Image 1